Adaptive arousal regulation: Pharmacologically shifting the peak of the Yerkes–Dodson curve by catecholaminergic enhancement of arousal - Lola Beerendonk; Jorge F. Mejías; Stijn A. Nuiten; Jan Willem de Gee; Jasper B. Zantvoord; Johannes J. Fahrenfort; Simon van Gaal (Proceedings of the National Academy of Sciences, 2025)
Performance typically peaks at moderate arousal levels, consistent with the Yerkes–Dodson law, as confirmed by recent human and mouse pupillometry studies. Arousal states are influenced by neuromodulators like catecholamines (noradrenaline and dopamine) and acetylcholine. To investigate their contributions to this law, we pharmacologically enhanced arousal while measuring human decision-making and spontaneous arousal fluctuations via pupil size. The catecholaminergic agent atomoxetine increased overall arousal and shifted the entire arousal–performance curve, suggesting a relative arousal mechanism where performance adapts to arousal fluctuations within arousal states. In contrast, the cholinergic agent donepezil did not measurably affect arousal or the curve. We modeled these findings in a neurobiologically plausible computational framework, showing how catecholaminergic modulation alters a disinhibitory neural circuit that encodes sensory evidence for decision-making. This work suggests that performance adapts flexibly to arousal fluctuations, ensuring optimal performance in each and every global arousal state.